Determinants of Work Absorption in East Kalimantan - Noviana Dipi Ramadhani; Syafitri , Wildan (Journal of Development Economic and Social Studies, 2025)
East Kalimantan is a province undergoing major development through the National Capital (IKN) project, yet it still faces employment challenges. Despite having relatively high levels of GRDP, wages, education, and both foreign (FDI) and domestic investment (DDI), the region continues to experience a high unemployment rate. This study aims to examine the influence of education, wages, GRDP, FDI, and DDI on labor absorption in 10 regencies/cities in East Kalimantan during the 2017–2023 period. The research employs a quantitative associative approach using secondary data analyzed through panel data regression with EViews software. The findings show that education has a negative and significant effect, while wages, GRDP, and DDI have positive and significant effects on labor absorption. Meanwhile, FDI has a negative but insignificant effect.